2018
DOI: 10.12681/jhvms.18018
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Intraocular Pressure (IOP) Regarding Circadian Rhythm, Age, Sex and Eye Side in Awassi Sheep

Abstract: Measurement of intraocular pressure (IOP) in domestic animals has become a part of routine eye examination with advent of applanation tonometer. Delayed control of high IOP may lead to permanent blindness due to retinal ganglion cells dysfunction and optic nerve degeneration. This study aimed at evaluating IOP of Awassi sheep with respect to circadian rhythm, age, sex and eye sides and finally to establish a reference (baseline, normal) IOP value for this particular species. A total of 24 healthy sheep with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…In some species, different IOP values were observed in healthy animals throughout the day. Possibly this fact stems from the influence of the circadian and adrenergic systems on the formation and regulation of aqueous humor 18,38,41 . In this study, significantly different IOP values were observed throughout the day, with both the rebound and applanation tonometers.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…In some species, different IOP values were observed in healthy animals throughout the day. Possibly this fact stems from the influence of the circadian and adrenergic systems on the formation and regulation of aqueous humor 18,38,41 . In this study, significantly different IOP values were observed throughout the day, with both the rebound and applanation tonometers.…”
Section: Discussionmentioning
confidence: 50%
“…Possibly this fact stems from the influence of the circadian and adrenergic systems on the formation and regulation of aqueous humor. 18,38,41 In this study, significantly different IOP values were observed throughout the day, with both the rebound and applanation tonometers. IOP values were higher at the beginning of the day (6:00 a.m.), decreasing from 9:00 a.m. and increasing again at 6:00 p.m., as previously described for New Zealand rabbits.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Several lines of evidence suggested that ocular rhythms may differ between sexes. The diurnal variation of intraocular pressure and tear production was shown to vary between sexes 29, 30 . Androgen, estrogen and progesterone receptor mRNA was found in a variety of ocular tissues 31, 32 .…”
Section: Discussionmentioning
confidence: 99%
“…To minimize factors that are known to alter IOP, the evaluations were performed by a single examiner, 7 using the same devices, 21 and under the same conditions of animal containment and environment 6,32 . Disruptions in IOP values related to circadian rhythm 33 were not considered in this study, given that the measurements were performed at the same time on both evaluation days. Nevertheless, although some variables can be controlled by a consistent technique, not all interference can be completely mitigated 7 …”
Section: Discussionmentioning
confidence: 99%